Inclusive Religious Education and Interfaith Interaction: Strengthening Religious Moderation through Teachers’ Lived Experiences in Multi-Religious State Schools - Setiawan, Agus; Ruslan; Ihlas; Ainun, Amma; Kusumawati, Yayuk (LETIGES, 2025)
The religious diversity in Indonesia requires a strong understanding of religious moderation, especially in educational settings. Religious moderation is crucial to fostering social harmony and preventing religion-based conflicts. This study aims to explore and understand how the reinforcement of religious moderation is implemented in religious education practices at State Senior High School 2 Donggo and State Junior High School 2 Donggo, located in Mbawa Village. The research employs a qualitative approach with a phenomenological design to examine the experiences of teachers and students in applying religious moderation values. The sample consists of 8 religious education teachers (Islam, Catholicism, and Protestantism) and 24 students from various religious backgrounds, selected purposively based on their involvement in religious education. Data was collected through semi-structured interviews and direct observations over one month in 2025. The data were analysed using thematic analysis techniques to identify key patterns related to religious moderation in learning. The findings indicate that strengthening religious moderation in education is carried out through integrating tolerance values into the curriculum, an inclusive approach in religious instruction, and harmonious social interactions among students of different faiths. This study highlights the role of education in fostering religious moderation through inclusive learning and interfaith dialogue. Its limitation lies in the narrow scope of two schools, which may affect generalizability. The originality of this study is its focus on teachers’ lived experiences as practical strategies for strengthening religious moderation, whereas previous studies mostly remained theoretical or policy-oriented.